A new ent-kaurane diterpene from Isodon henryi. Issue 14 (29th June 2021) - Jiang, Xue; Zhang, Ling-Xia; Feng, Qing-Mei; Wu, Hong; Liu, Ya-Lin; Wang, De-Qin; Dai, Li-Ping; Wang, Zhi-Min
Abstract: One new ent -Kaurane diterpenoid (1 ) was isolated from the ethyl acetate fraction of Isodon henryi . Along with ten diterpenoids (2–11 ) were isolated from this plant for the first time, including six 7, 20-epoxy diterpenoids, three enmenol-type diterpenoids and one 6, 7-seco- ent -kaurene diterpenoid. Their structures were elucidated by 1 D and 2 D NMR, confirmed by HRESIMS and electronic circular dichroism analyses. Furthermore, the cytotoxicities of twelve compounds were investigated in five human cancer cell lines, including A2780, BGC-823, HCT-116, HepG2 and HeLa. And the IC50 values of these diterpenoids ranged from 2.1 to 88.8 μM in the tested cell lines. Based on the molecular structures of 12 compounds and the bioassay results, it suggests that α, β -unsaturated pentanone is the cytotoxic active site of 7, 20 epoxy ent -kaurane diterpenoid, but it does not contribute much to enmenol-type diterpenoid. Supplemental data for this article can be accessed at https://doi.org/10.1080/14786419.2019.1675067 . Graphical Abstract: Supplemental data for this article can be accessed at https://doi.org/10.1080/14786419.2019.1675067 .